2000
DOI: 10.1136/oem.57.9.595
|View full text |Cite
|
Sign up to set email alerts
|

Updated mortality among diverse operating segments of a petroleum company

Abstract: Objectives-To update mortality for 34 560 employees from diverse operating segments of a Canadian petroleum company; and to investigate potential relations with occupational factors. Methods-Employees from 1964-83 were linked to the Canadian mortality data base to provide 11 years additional follow up. There were 6760 deaths and 750 683 person-years of follow up compared with 3909 and 428 190, respectively, in the earlier study. Analyses used standardised mortality ratios (SMRs) to compare worker cause specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…148 In a cohort of petroleum workers exposed to gasoline, Wong et al 152 observed a nonsignificant inverse association (SMR 5 0.79, 95% CI: 0.46-1.24) based on 17 observed cases.…”
Section: Organic Solventsmentioning
confidence: 99%
“…148 In a cohort of petroleum workers exposed to gasoline, Wong et al 152 observed a nonsignificant inverse association (SMR 5 0.79, 95% CI: 0.46-1.24) based on 17 observed cases.…”
Section: Organic Solventsmentioning
confidence: 99%
“…Thirty-five studies examined the risk of NHL among workers exposed to gasoline (Table 1) [7][8][9]11,12,. Most were conducted in North America [7][8][9]11,[17][18][19][20][21]23,24,[28][29][30]32,33,37,39,40,42,44]; six in Scandinavia [25][26][27]36,38,41] and Europe [16,22,31,35,43,45]; and two in Australia/New Zealand [12,34].…”
Section: Resultsmentioning
confidence: 99%
“…In another two papers by Lewis et al [10], this time studying a Canadian petroleum company, the later-dated article reported the risk in the cohort as a whole while we referred to the earlier one as it focused on risks by operating segment where exposures were likely to differ [11]. For two cohorts of petroleum workers [11,12], additional findings were reported by benzene exposure levels using a nested case-control design [13,14].…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Numerous mortality and incidence studies assessing this association have been performed mainly in benzene-exposed workers from the production of natural rubber film [139][140][141][142], shoe-producing industry [143,144] and the petroleum industry [19,20,[145][146][147][148][149][150][151][152][153][154][155][156][157], but other industries and occupations have also been examined [90,[158][159][160]. Table 3 provides an overview of studies that includes estimates of the quantitative risk of benzene exposure.…”
Section: Leukemiamentioning
confidence: 99%